Positive Correlation between Tyrosine Phosphorylation of CpsD and Capsular Polysaccharide Production in Streptococcus pneumoniae - Bender, Matthew H. (American Society for Microbiology, 2003)
CpsA, CpsB, CpsC, and CpsD are part of a tyrosine phosphorylation regulatory system involved in modulation of capsule synthesis in Streptococcus pneumoniae and many other gram-positive and gram-negative bacteria. Using an immunoblotting technique, we observed distinct laddering patterns of S. pneumoniae capsular polysaccharides of various serotypes and found that transfer of the polymer from the membrane to the cell wall was independent of size. Deletion of cps2A, cps2B, cps2C, or cps2D in the serotype 2 strain D39 did not affect the ability to transfer capsule to the cell wall. Deletion of cps2C or cps2D, which encode two domains of an autophosphorylating tyrosine kinase, resulted in the production of only short-chain polymers. The function of Cps2A is unknown, and the polymer laddering pattern of the cps2A deletion mutants appeared similar to that of the parent, although the total amount of capsule was decreased. Loss of Cps2B, a tyrosine phosphatase and a kinase inhibitor, resulted in an increase in capsule amount and a normal ladder pattern. However, Cps2B mutants exhibited reduced virulence following intravenous inoculation of mice and were unable to colonize the nasopharynx, suggesting a diminished capacity to sense or respond to these environments. In D39 and its isogenic mutants, the amounts of capsule and tyrosine-phosphorylated Cps2D (Cps2D∼P) correlated directly. In contrast, restoration of type 2 capsule production followed by deletion of cps2B in Rx1, a laboratory passaged D39 derivative containing multiple uncharacterized mutations, resulted in decreased capsule amounts but no alteration in Cps2D∼P levels. Thus, a factor outside the capsule locus, which is either missing or defective in the Rx1 background, is important in the control of capsule synthesis.